From Carlos Eugênio to codinome clemente, interview with ISA Albuquerque - Sarmento-Pantoja, Augusto; Sarmento-Pantoja, Tânia [UNESP] (Universidade Federal do Para, 2021)
Interview held on October 15, 2020, as an activity of the VII International Seminar on Literature and Resistance Film (SELCIR). The interview was conducted by PhD. Augusto Sarmento-Pantoja and had the collaboration of PhD. Tânia Sarmento-Pantoja and the participation of Filmmaker Isa Albuquerque and researcher and widow of Carlos Eugênio, PhD. Maria Cláudia Badan Ribeiro. Below we transcribe some passages from the interview with Isa Albuquerque. The full interview is available on video https://www.youtube.com/watch?v=O9LQuU0pKs Q.
De Carlos Eugênio à codinome clemente, entrevista com ISA Albuquerque
Keywords: Codinome clemente; Censorship; Cinema; Resistance